PROBLEM SOLVING ON INTEGRAL CALCULUS WITH THE ASSISTANCE OF LECTURERS TUTORS, GOOGLE SEARCH, AND ARTIFICIAL INTELLEGANCE TUTORS: PHENOMENOLOGY STUDY ON PROSPECTIVE MATHEMATICS TEACHER - Subroto, Toto; Kharimah, Nurul Ikhsan; Yulianto, Eko (Journal of Authentic Research on Mathematics Education (JARME), 2023)
This study reveals how prospective teacher students solve Integral Calculus problems with three different assistances, namely the Assistance of Lecturer Tutors, Google Search Tutors, and Artificial Intelligent (AI) Tutors through Socratic Application. This study used a qualitative approach with phenomenological methods to reveal participants' learning experiences. Research participants consisted of nine people who were divided into three groups with different assistance. The data obtained were in the form of recorded discussions, interviews, recorded cellphone screens, and artifacts of student answers. All data is analyzed based on the activity of the respondents in seeking and finding answers. The research findings show that students who study with the help of lecturer tutors are more careful in proposing assistance from the search and sorting of answers stage. While students who use AI and Google Search have almost the same characteristics in starting a search, but at the stage of sorting answers,Â  AI is thought as able to provide more efficient and accurate recommendations answers.